2021
DOI: 10.1109/tgrs.2020.3023085
|View full text |Cite
|
Sign up to set email alerts
|

On the Abundance and Common Properties of Continental, Organized Shallow (Green) Clouds

Abstract: Warm convective clouds play a significant role in the earth's energy and water budgets. However, they still pose a challenge in climate research as their feedback to predicted thermodynamic changes is highly uncertain and considered critical to the overall climate system's response. The focus of this study is continental, organized shallow convective clouds that, although they are spread globally and form in a variety of environments, seem to have common properties. One of these properties seems to be their pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…2.2) and exhibit a regular (grid-like) pattern, which is a high level of organization. This type of organization is typical for green Cu fields (Dror et al, 2020) and was reported in several continental areas, e.g., the Amazon basin (Da Silva et al, 2011;Heiblum et al, 2014), the US Southern Great Plains (Hinkelman and Evans, 2004), and northern Germany (Müller et al, 1985). However, due to the presence of GWs, the curve of the observed NNCDF of subdomain-2 lies closer to the diagonal and leans more towards clustered organization, resulting in a larger I org comparing to that of subdomain-1 (I org = 0.44 and I org = 0.35, respectively).…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…2.2) and exhibit a regular (grid-like) pattern, which is a high level of organization. This type of organization is typical for green Cu fields (Dror et al, 2020) and was reported in several continental areas, e.g., the Amazon basin (Da Silva et al, 2011;Heiblum et al, 2014), the US Southern Great Plains (Hinkelman and Evans, 2004), and northern Germany (Müller et al, 1985). However, due to the presence of GWs, the curve of the observed NNCDF of subdomain-2 lies closer to the diagonal and leans more towards clustered organization, resulting in a larger I org comparing to that of subdomain-1 (I org = 0.44 and I org = 0.35, respectively).…”
mentioning
confidence: 80%
“…Continental shallow Cu clouds, often forming during the summer season (Zhang and Klein, 2013) or dry season in the tropics, are observed in a variety of locations -low, mid, and high latitudes -and are preferably formed over forests and vegetated areas; therefore, they are referred to as "green Cu" (Dror et al, 2020). These continental clouds in general, and specifically their organization, are by far less studied than their maritime counterparts, i.e., trade Cu.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2.2) and exhibit a regular (grid-like) pattern, which is a high level of organization. This type of organization is typical for green Cu fields (Dror et al, 2020) and was reported in several continental areas, e.g., the Amazon basin (Da Silva et al, 2011;Heiblum et al, 2014), the Southern Great Plains (Hinkelman and Evans), and Northern Germany (Müller et al, 1985). However, due to the presence of GW, the curve of the observed NNCDF of subdomain-2 lies closer to the diagonal, and leans more towards clustered organization, resulting in a larger I org comparing to that of subdomain-1 (I org = 0.43 and I org = 0.34, respectively).…”
mentioning
confidence: 80%